Adult outcomes of being born late preterm or early term – What do we know?. Issue 1 (February 2019) - Kajantie, Eero; Strang-Karlsson, Sonja; Evensen, Kari Anne Indredavik; Haaramo, Peija
Abstract: The literature on adult outcomes of people born late preterm (LPT, 34–36 completed weeks) or early term (ET, 37–38 weeks) was reviewed. In PubMed, 9547 articles were identified; 53 were eligible. Of these, 12 were based on clinical cohorts, 32 on medical birth register linkages, and nine on historical birth cohorts; 48 out of 53 on Nordic countries; 50 out of 53 reported on LPT and eight out of 53 reported on ET. LPT plus ET have increased early (<45 years) adult all-cause mortality. Despite increased cardiometabolic risk factors and slightly lower cardiorespiratory fitness in LPT, no studies showed increased risk for coronary heart disease, some showed increased risk for stroke, and all showed increased risk for type 2 diabetes. Most show increased risk for asthma and decreased allergic rhinitis. LPT have slightly lower cognitive abilities and higher rates of several mental disorders; ET have intermediate values. LPT and ET adults have slightly lower education, occupational status, and income. We recommend that authors report findings of LPT/ET separately from those born more preterm.